Evaluation of the Programme of Mechanisation of Fishing Boats State Reports - Planning Commission (Planning Commission, 1971)
Andhra Pradesh popularly called the ’River State’ has two most important inter-state rivers -viz., the Godavari and the Krishna which flow through the heart of the state along with their numerous tributaries. These rivers, streams, tanks and ponds provide ample scope for development of inland fisheries. The state has an estimated inland water area of about 9.2 lakh hectares out of which culturable area is approximately 4 lakh hectares. The Bay of Bengal forms the eastern boundary of the State providing it with a long coast line of 960 kms.
Programme Evaluation Organisation, Planning Commission, Government of India